Panorama of Intimate Partner Violence Against Women in Brazil and its Association With Self-Perception of Health: Findings From a National Representative Survey. Issue 13 (July 2023) - Signorelli, Marcos Claudio; de Souza, Felipe Granado; Pinheiro Junior, Raimundo Valdemy Borges; Valente, Juliana; Andreoni, Solange; Rezende, Leandro Fórnias Machado de; Sanchez, Zila Van Der Meer
Intimate partner violence (IPV) is a challenge in Brazil. The country holds one of the highest rates of femicide in the world, most of which are preceded by IPV. We conducted a cross-sectional study with 34, 334 women, aged 18 to 59 years, from the 2019 Brazilian National Health Survey to analyze the prevalence of IPV and its subtypes among the Brazilian adult women in the last 12 months, encompassing their health consequences and the use of health services resulting from IPV. We also used logistic regression models to estimate the association of sociodemographic characteristics and self-perceived health status with IPV. The prevalence of IPV among Brazilian adult women in the last 12 months was 7.6% (95% confidence interval [CI] [7.0, 8.2]). Women aged 18 to 39 years, not married, and with income of up to 1 minimum wage (MW), had higher odds of suffering IPV. Among those who reported health consequences due to IPV, 69% reported psychological consequences, and 13.9% sought health care, mostly in primary or secondary health care services in the Brazilian Unified Health System (41.9%). Regarding the self-perceived health variables, women who reported eating problems (odds ratio [OR] = 1.29; [1.01, 1.65]), lack of interest/absence of pleasure (OR = 1.41; [1.11, 1.79]), depressive feelings (OR = 1.39; [1.03, 1.88]), feeling of failure (OR = 1.75; [1.36, 2.24]), and suicidal thoughts (OR = 1.73; [1.25, 2.41]) had greater odds of reporting IPV compared to those who did not report these same perceptions. The results show that younger, divorced or single, low-income women with eating problems and mental health disorders were more likely to suffer IPV. IPV often led to health problems, and many abused women sought support from public health services. Health professionals must be trained to identify and care for these women, thereby acting as allies in preventing and reducing IPV.